A species of Megaphragma (Hymenoptera: Chalcidoidea: Trichogrammatidae), one of the smallest known insects, new for Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
A species of Megaphragma, new for Italy, has been collected withyellow sticky traps placed in a vineyard in Southern Italy (Basilicata). A preliminarydescription of this species, which belongs to the group ghesquierei Nowickiand is probably new to science, is given.
Keywords: thrips; egg-parasitoid; vineyard